Comparison of basal insulin therapies with regard to the risk of acute myocardial infarction in patients with type 2 diabetes: an observational cohort study. Issue 12 (5th October 2015) - Kollhorst, B.; Behr, S.; Enders, D.; Dippel, F.‐W.; Theobald, K.; Garbe, E.
Abstract : Aims: To assess the risk of acute myocardial infarction (AMI) in patients with type 2 diabetes mellitus treated with long‐acting insulin analogues in comparison with other basal insulin therapy. Methods: We used German insurance claims data from the years 2004–2009 to conduct a study in a retrospective cohort of patients with type 2 diabetes. Naïve insulin users were defined as patients who had an insulin‐free history before the first prescription of long‐acting analogue insulin, human NPH insulin or premixed insulin and who were pretreated with oral antidiabetic drugs. Adjusted hazard ratios (HRs) of AMI and corresponding 95% confidence intervals (CIs) were calculated using sex‐stratified Cox models. Propensity‐score‐matched analyses were conducted as sensitivity analyses. Results: We identified 21 501 new insulin users. Patients treated with premixed insulin were older than patients treated with analogue or NPH insulin (mean age 70.7 vs. 64.1 and 61.6 years, respectively) and had more comorbidities. Regarding the risk of AMI, adjusted HRs showed no statistically significant difference between NPH and analogue insulin (HR 0.94, 95% CI 0.74–1.19), but a higher risk for premixed than for analogue insulin (HR 1.27, 95% CI 1.02–1.58). Contrary to the primary analysis, the propensity‐score‐matched analysis did not show an increased risk for premixed insulin. Conclusions: In contrast to a former database study, no difference was observed for the risk of AMI between long‐acting analogue and NPH insulin in this study. Neither long‐acting analogue insulin nor premixed insulin appears to be associated with AMI in patients with type 2 diabetes.